Implementation of Inquiry Model Integrated Ethno-STEM On Volatile Organic Compounds (VOC) Herbal Tea for Downstreaming the Brilliance of UNNES Education and Student Conservation Character. - Sudarmin Sudarmin; K. Kasmui; S. Diliarosta; W. Sumarni; Rr. S.E Pujiastuti (International Conference on Science, Education, and Technology, 2023)
The purpose of this study was to determine students' responses to the application of the integrated Ethno-STEMinquiry learning model for volatile organic compounds from herbal teas and mastery of the concept of learning outcomes in ethnoscience and local wisdom. This research is part of research funding expertise research for the 2023 fiscal year. The research begins in 2022 by (1) developing an ethno-STEM integrated inquiry learning model with Sudarmin syntax through the define, design, and development stages, (2) preparing research instruments for students' responses to Ethno-STEM integrated inquiry learning model for study materials of volatile organic compounds in herbal teas. In this study, data was collected related to the Ethno-STEM integrated inquiry learning model that had been developed. The research subjects were science education students taking Ethnoscience and Local Crafts courses at the Faculty of Mathematics and Natural Sciences (FMIPA) Semarang State University. At the end of the implementation of the Ethno-STEM integrated inquiry learning model with the Sudarmin syntax, data analysis of student responses to the learning process and outcomes was carried out. The results of the study concluded (a) students' concept mastery scores still needed to be improved, because based on the N-gainscore there were still many moderate categories, (b) understanding of organic volatile compounds in herbal teas, trapping tools for organic volatile compounds from herbal teas reached a good category, ( c) The overall results of learning activities show a positive response to the developed model.